2009
DOI: 10.1016/j.cub.2009.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Confusions Show that Facial Expressions Are Not Universal

Abstract: Central to all human interaction is the mutual understanding of emotions, achieved primarily by a set of biologically rooted social signals evolved for this purpose-facial expressions of emotion. Although facial expressions are widely considered to be the universal language of emotion, some negative facial expressions consistently elicit lower recognition levels among Eastern compared to Western groups (see [4] for a meta-analysis and [5, 6] for review). Here, focusing on the decoding of facial expression sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
456
10
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 484 publications
(519 citation statements)
references
References 28 publications
47
456
10
6
Order By: Relevance
“…Thus, the input mechanisms, or psychological 'mills', that modulate social learning have characteristics that are culturally inherited-e.g. offspring inherit from their cultural parents a tendency to focus on the eyes, or on the eyes and mouth, when viewing facial expressions of emotion [31]-and these mill characteristics influence the 'grist' that is culturally inherited through social learning-e.g. beliefs about what kinds of foods are and are not disgusting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the input mechanisms, or psychological 'mills', that modulate social learning have characteristics that are culturally inherited-e.g. offspring inherit from their cultural parents a tendency to focus on the eyes, or on the eyes and mouth, when viewing facial expressions of emotion [31]-and these mill characteristics influence the 'grist' that is culturally inherited through social learning-e.g. beliefs about what kinds of foods are and are not disgusting.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Jack et al [31] used eye movement tracking to measure attention to emotional faces in Western Caucasian and East Asian participants. Across all emotion types and face ethnicities, they found that Western Caucasians divided their attention more equally between the eyes and mouth than the East Asians, who focussed more on the eyes.…”
Section: Social Learningmentioning
confidence: 99%
“…Specifically, the universality hypothesis proposes that six basic internal human emotions (i.e., happy, surprise, fear, disgust, anger, and sad) are expressed using the same facial movements across all cultures (4-7), supporting universal recognition. However, consistent cross-cultural disagreement about the emotion (8)(9)(10)(11)(12)(13) and intensity (8)(9)(10)(14)(15)(16) conveyed by gold standard universal facial expressions (17) now questions the universality hypothesis.…”
mentioning
confidence: 99%
“…It may be possible to investigate if other cultures use different areas of the face for NVC perception, based on feature selection. Gaze patterns are culturally dependent for emotion recognition [12]. However, humans may be using different areas of the face for recognition compared to an automatic system, and the current feature extraction process is not expected to be as comprehensive as human perception.…”
Section: Analysis: Visualising Selected Feature Subsetsmentioning
confidence: 99%
“…[2]), which can make comprehension of the overall distribution difficult. In experimental psychology, gaze patterns in perception have been visualised by Jack et al [12].…”
Section: Introductionmentioning
confidence: 99%